Intention to Purchase Counterfeit Luxury Products: A Comparative Study Between Pakistani and the UK Consumers. Issue 5 (20th October 2017) - Hussain, Ammar; Kofinas, Alexander; Win, Sandar
ABSTRACT: This study compares Pakistani and the UK consumers' purchase intentions toward counterfeit luxury products by focusing on the relationships between the following four factors: perceived quality, status consumption, low price, and ethics. Two samples of students from the UK (114) and Pakistan (137) were surveyed for comparative purposes. Data were analyzed by using AMOS and SPSS. The results show that while Pakistani consumers are satisfied with the perceived quality of counterfeit products, the UK consumers are not. The status associated with counterfeit products and price of the products were identified as important factors for both populations. However, Pakistani consumers exhibit less ethical behavior compare to the UK consumers. Thus, the study provides evidence that intention for purchasing counterfeit luxury products differs between the two populations and thus companies may have to differentiate their strategies in tackling the problem in developing and developed countries. Selecting a single product category and a single range of products may restrict generalizability.